The Distributed University for Sustainable Higher Education - Heller, Richard Frederick (SpringerBriefs in Education, 2022)
This book is open access and discusses the re-imagining of the higher education sector. It exposes problems that relate to the way that universities have become over-managed business enterprises which may not reflect societal, national, or global educational needs. From there, it proposes some solutions, including three innovative programs, that make universities more responsive to needs, as well as reduce their impact on the environment. The central idea of this book is developing the 'Distributed University,' which distributes education to where it is needed, reducing local and global inequalities in access, and emphasizing local relevance in place of large centralized campuses, with a low impact on the environment. It emphasizes the distribution of trust in place of managerialism and collaboration in place of competition. By focusing on distributing education online, this book discusses how the higher education sector can be set up to adapt to the changes in the ways we work and learn today, and which will be required to adapt to and take advantage of the Fourth Industrial Revolution.